A high temperature stable positive electrode material and its preparation method and application
By coating the composite oxide and difluorophosphate on the surface of lithium nickel-cobalt-manganese oxide, a multi-layer structure is formed, which solves the problem of unstable high-nickel ternary positive electrode material at high temperatures, and achieves high voltage and high capacity And the improvement of high-temperature cycling performance, it is suitable for high-performance batteries such as electric vehicles.
Patent Information
- Application Number
- CN202210004417.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-04
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-01-04
AI Technical Summary
The high-nickel ternary cathode materials of existing lithium-ion batteries are unstable at high temperatures, and are prone to nickel-lithium mixed discharge and structural corrosion, resulting in reduced electrochemical performance and safety hazards, making it difficult to meet high-performance needs such as electric vehicles.
The composite oxide is used to coat lithium nickel cobalt manganese-based oxides and difluorophosphate is coated on the surface of the composite oxide to form a multi-layer structure to improve the high temperature stability and electrochemical properties of the material.
It significantly improves the battery's high temperature stability and cycling performance at high voltages, enhances capacity retention and rate performance, reduces safety risks, and is suitable for high-power electric devices.
Smart Images

Figure CN114400320B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a high-temperature stable positive electrode material and a preparation method and application thereof. Background Art
[0002] With the progress of economic globalization and the continuous increase in energy demand, the search for new energy storage devices has become a hot topic in the field of new energy. Compared with traditional batteries, lithium-ion batteries not only have higher energy, stronger discharge capacity, longer cycle life, but also have an energy storage efficiency of more than 90%. The above characteristics determine that lithium-ion batteries have great development prospects in electric vehicles, storage power sources, etc.
[0003] Currently, commercial power lithium-ion batteries are mainly lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate and nickel cobalt manganese ternary batteries. Among them, ternary batteries have gradually become mainstream products due to their higher capacity, but the capacity is still difficult to meet the increasingly high performance requirements of electric vehicles.
[0004] The modification research of ternary batteries is the mainstream of the current market, with high nickel ternary batteries as the core direction. The nickel-cobalt-manganese ternary positive electrode material crystal belongs to the hexagonal system and is α-NaFeO 2 Layered structure has gradually become the mainstream choice for positive electrode materials of lithium-ion batteries due to its excellent properties. Among them, high-capacity high-nickel ternary positive electrode materials (Ni molar fraction greater than 0.6) are the most widely studied. The battery capacity of high-nickel ternary batteries is further improved due to their high nickel content, but the resulting nickel-lithium mixing phenomenon and instability are more obvious, which is not conducive to the application of this material in actual high-power electric devices.
[0005] At present, the instability of lithium ion batteries at high temperatures has been studied in depth. The main electrolyte lithium salt in lithium ion batteries is LiPF. 6 It is very sensitive to trace amounts of water. The main electrolyte lithium salt in lithium-ion batteries is LiPF 6 , which is very sensitive to trace amounts of water. 6 The thermal stability is poor and it is easy to react with water to produce HF, which will corrode the positive electrode material, causing the dissolution of metal ions in the material and destroying the material structure, thus deteriorating the electrochemical performance of the material. As the nickel content increases, the lithium ions migrating on the surface of the active material are very likely to react with the coated carbonate to form lithium carbonate, increasing the loss of irreversible capacity. In addition, the lithium carbonate inside the SEI film decomposes at high temperatures, causing the SEI film to fall off, which is very likely to cause battery bloating, posing a great safety hazard.
[0006] Since the electrode reaction of lithium-ion batteries occurs at the electrode / electrolyte interface, surface coating modification of ternary materials is an effective method to improve their electrochemical performance. The coating layer can prevent the main material from directly contacting the electrolyte, thereby enhancing thermal stability and corrosion resistance, improving its capacity retention rate, and improving rate performance. However, the effect of the coating layer on electrode performance is highly dependent on the performance, content, and processing conditions of the coating layer. Coating with oxides such as aluminum oxide can reduce the contact between the electrode and the electrolyte, thereby effectively reducing the corrosion of the electrolyte to the electrode, and to some extent, can inhibit its structural instability; however, coating with oxides such as aluminum oxide makes it difficult to control the residual alkali content on the surface of the precursor and the high-temperature gas production, and it is difficult to maintain a stable structure of the electrode material under high pressure and high temperature conditions.
[0007] Therefore, there is an urgent need to provide a positive electrode material with high voltage and high temperature stability. Summary of the invention
[0008] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a high-temperature stable positive electrode material and a preparation method and application thereof, and the battery prepared by using the positive electrode material has the characteristics of high voltage, high capacity and high-temperature stability.
[0009] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a high-temperature stable positive electrode material, which includes a lithium nickel cobalt manganese-based oxide, a composite oxide and a difluorophosphate; the composite oxide is coated on the surface of the lithium nickel cobalt manganese-based oxide; the difluorophosphate is coated on the surface of the composite oxide; the composite oxide includes oxygen and at least two metal elements of aluminum, titanium, zirconium, yttrium, tungsten, silicon, boron, magnesium, niobium, lanthanum, zinc, tin, calcium or bismuth.
[0010] The lithium nickel cobalt manganese-based oxide has a hexagonal layered structure and a space group of R-3m.
[0011] The composite oxide is coated on the surface of the lithium nickel cobalt manganese-based oxide, and the difluorophosphate is coated on the surface of the composite oxide, which can improve the high temperature stability of a battery using the positive electrode material at a high voltage.
[0012] According to some embodiments of the present invention, the difluorophosphate is lithium difluorophosphate.
[0013] According to some embodiments of the present invention, the composite oxide further includes lithium.
[0014] According to some embodiments of the present invention, the composite oxide includes oxygen and at least two metal elements selected from the group consisting of aluminum, titanium, zirconium, yttrium, tungsten, silicon, boron, magnesium, niobium or lanthanum.
[0015] According to some embodiments of the present invention, the composite oxide is at least two metal oxides.
[0016] The metal oxide is a binary compound composed of oxygen and a metal element selected from aluminum, titanium, zirconium, yttrium, tungsten, silicon, boron, magnesium, niobium or lanthanum.
[0017] According to some embodiments of the present invention, the composite oxide is two metal oxides.
[0018] According to some embodiments of the present invention, the composite oxide is Al 2 O 3 and TiO 2 .
[0019] According to some embodiments of the present invention, the composite oxide is La 2 O 3 and TiO 2 .
[0020] According to some embodiments of the present invention, the composite oxide is Al 2 O 3 、TiO 2 、ZrO 2 , Y 2 O 3 , WO 3 、LiWO 3 、SnO、Bi 2 O 3 , B 2 O 3 , CaO, La 2 O 3 、SiO 2 、MgO、LiMgWO 5 MgAl 2 O 4 At least one of;
[0021] According to some embodiments of the present invention, the general chemical formula of the lithium nickel cobalt manganese-based oxide is LiNi x Co 1-x- y Mn y O 2 ; x is 0.3-0.8; y is 0.1-0.6; 1-xy is 0.01-0.4.
[0022] According to some embodiments of the present invention, the general chemical formula of the lithium nickel cobalt manganese-based oxide is LiNi x Co 1-x- y Mn y O 2; x is 0.35-0.75; y is 0.14-0.50; 1-xy is 0.01-0.35.
[0023] According to some embodiments of the present invention, the chemical formula of the lithium nickel cobalt manganese-based oxide is LiNi 0.75 Co 0.1 Mn 0.15 O 2 、LiNi 0.75 Co 0.1 Mn 0.15 O 2 or LiNi 0.35 Co 0.15 Mn 0.55 O 2 .
[0024] According to some embodiments of the present invention, the positive electrode material includes lithium nickel cobalt manganese-based oxide, composite oxide and difluorophosphate in a molar ratio of 1:(0.001-0.05):(0.001-0.03).
[0025] According to some embodiments of the present invention, the positive electrode material includes the lithium nickel cobalt manganese-based oxide, the composite oxide and the difluorophosphate in a molar ratio of 1:(0.001-0.03):(0.001-0.02).
[0026] According to some embodiments of the present invention, the positive electrode material includes the lithium nickel cobalt manganese-based oxide, the composite oxide and the difluorophosphate in a molar ratio of 1:(0.01-0.03):(0.001-0.02).
[0027] According to some embodiments of the present invention, the positive electrode material includes the lithium nickel cobalt manganese-based oxide, the composite oxide and the difluorophosphate in a molar ratio of 1:0.01:0.005.
[0028] According to some embodiments of the present invention, the positive electrode material includes the lithium nickel cobalt manganese-based oxide, the composite oxide and difluorophosphate in a molar ratio of 1:0.015:0.02.
[0029] According to some embodiments of the present invention, the positive electrode material includes the lithium nickel cobalt manganese-based oxide, the composite oxide and difluorophosphate in a molar ratio of 1:0.03:0.01.
[0030] A second aspect of the present invention provides a method for preparing the above-mentioned positive electrode material, the preparation method comprising the following steps:
[0031] (1) under an inert atmosphere, adding a sol of a precursor of at least two elements selected from aluminum, titanium, zirconium, yttrium, tungsten, silicon, boron, magnesium, niobium, lanthanum, zinc, tin, calcium or bismuth to a lithium nickel cobalt manganese-based oxide in the form of a spray, stirring at a rate of 600-1500 rpm / min, heating to 80-120° C., and drying for 2-4 hours;
[0032] (2) In an oxygen atmosphere, heating to 250-450° C. with stirring at a rate of 50-200 rpm / min and keeping the temperature for 2-6 hours;
[0033] (3) Under an inert atmosphere, cool to 30-50° C., add difluorophosphate, stir at a rate of 600-1500 rpm / min, and mix for 15-90 min; and obtain the positive electrode material.
[0034] The precursor includes at least two elements of aluminum, titanium, zirconium, yttrium, tungsten, silicon, boron, magnesium, niobium, lanthanum, zinc, tin, calcium or bismuth.
[0035] According to some embodiments of the present invention, the difluorophosphate is lithium difluorophosphate.
[0036] According to some embodiments of the present invention, the precursor includes at least one of a metal oxide, a hydroxide, a composite oxide and / or an oxyhydroxide.
[0037] According to some embodiments of the present invention, the precursor is Al 2 O 3 、TiO 2 , Li 2 WO 4 Mg(OH) 2 , LaOOH or TiO(OH) 2 At least two of the .
[0038] According to some embodiments of the present invention, the sol is an aqueous sol or an alcohol sol.
[0039] According to some embodiments of the present invention, the solid content of the sol is 5-30 wt %.
[0040] According to some embodiments of the present invention, the solid content of the sol is 8-25 wt %.
[0041] According to some embodiments of the present invention, the sol is Al 2 O 3 With TiO 2 Aqueous or alcoholic sol.
[0042] According to some embodiments of the present invention, the sol is Li 2 WO 4 With Mg(OH)2 Aqueous or alcoholic sol.
[0043] According to some embodiments of the present invention, the sol is LaOOH and TiO(OH) 2 Aqueous or alcoholic sol.
[0044] According to some embodiments of the present invention, the oxygen volume concentration in the oxygen atmosphere is 20%-99.9%; the air pressure is 0.1-0.3 MPa.
[0045] According to some embodiments of the present invention, the inert atmosphere is a nitrogen atmosphere; preferably, the volume concentration of nitrogen in the inert atmosphere is above 99.9%; and the gas pressure is 0.1-0.3 MPa.
[0046] A second aspect of the present invention provides an electrode slurry, wherein the electrode slurry comprises the above-mentioned positive electrode material, and the positive electrode material is prepared by the above-mentioned preparation method.
[0047] A third aspect of the present invention provides an electrode sheet, comprising a current collector and an electrode coating disposed on the current collector; the electrode coating is made from the above-mentioned electrode slurry.
[0048] According to some embodiments of the present invention, the current collector is aluminum foil.
[0049] A fourth aspect of the present invention provides a method for preparing an electrode sheet, the method comprising the following steps: coating the electrode slurry on the surface of a current collector, drying, and heat treating to obtain the electrode sheet.
[0050] A fifth aspect of the present invention provides use of the above-mentioned positive electrode material in preparing a battery.
[0051] According to some embodiments of the present invention, the battery is a lithium-ion battery.
[0052] Therefore, the beneficial effects of the present invention include:
[0053] 1. The cathode material of the present invention coats the composite oxide on the surface of the lithium nickel cobalt manganese-based oxide, and coats the difluorophosphate on the surface of the composite oxide, which effectively inhibits the deterioration of the electrochemical performance of the cathode battery due to chemical changes under high voltage cycling. The battery prepared by using the composite oxide has the characteristics of high capacity, high rate, good high temperature cycling performance and good high temperature stability under high voltage;
[0054] 2. The preparation method of the positive electrode material of the present invention is simple and easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a scanning electron microscope image of the positive electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the technical solutions in the embodiments of the present invention are clearly and completely described below.
[0057] Example 1
[0058] This embodiment provides a positive electrode material, the raw material components for preparing the positive electrode material include 1 kg of lithium nickel cobalt manganese-based oxide, 80 g of ( Al 2 O 3 ) 0.6 .(TiO 2 ) 0.4 Alcohol phase sol and 27.38g of lithium difluorophosphate.
[0059] The lithium nickel cobalt manganese-based oxide is LiNi 0.75 Co 0.1 Mn 0.15 O 2 , provided by Guangdong Brunp Recycling Technology Co., Ltd.
[0060] Should ( Al 2 O 3 ) 0.6 .(TiO 2 ) 0.4 The solid content of the alcohol phase sol is 10wt%.
[0061] The stoichiometric formula of the cathode material is LiNi 0.75 Co 0.1 Mn 0.15 O 2 ﹒ 0.015((Al 2 O 3 ) 0.6 (TiO 2 ) 0.4 )·0.02LiPO 2 F 2 .
[0062] The preparation method of the positive electrode material is:
[0063] (1) Place lithium nickel cobalt manganese-based oxide in a high-speed mixer, start nitrogen protection (pressure of 0.2 MPa), and continuously stir at a speed of 1200 rpm / min; ( Al 2 O 3 ) 0.6 .(TiO 2 ) 0.4 Add the alcohol phase sol in the form of spray and stir evenly at low speed; heat to 80℃ and dry for 2h;
[0064] (2) stirring at a low speed in an oxygen atmosphere (oxygen concentration of 20%), gradually heating to 350°C, keeping the temperature for 3 hours, and then cooling;
[0065] (3) When the temperature is lowered to 30° C., lithium difluorophosphate is added with high-speed stirring under a nitrogen atmosphere, and stirring is continued for 90 minutes to obtain the positive electrode material.
[0066] The present embodiment also provides a soft-pack battery, which uses the positive electrode material provided in the present embodiment as the positive electrode material, PVDF as the binder, activated carbon as the conductive agent, the mass percentage of the three is 96:2:2, N-methylpyrrolidone is used as the solvent, and is stirred into a slurry; the slurry is evenly coated on an aluminum foil by a coating machine, and is made into a positive electrode sheet after drying, the electrolyte is 1.02 mol / L lithium hexafluorophosphate, DMC / EMC, PC solvents and other additives; graphite is used as the negative electrode to make a soft-pack battery.
[0067] Example 2
[0068] This embodiment provides a positive electrode material, the raw material components for preparing the positive electrode material include 1 kg of lithium nickel cobalt manganese-based oxide, 50 g of (Li 2 WO 4 ) 0.5 .(Mg(OH) 2 ) 0.5 Aqueous sol and 27.38 g of lithium difluorophosphate.
[0069] The lithium nickel cobalt manganese-based oxide is LiNi 0.55 Co 0.01 Mn 0.49 O 2 , provided by Guangdong Brunp Recycling Technology Co., Ltd.;
[0070] (Li 2 WO 4 ) 0.5 .(Mg(OH) 2 ) 0.5 The solid content in the aqueous sol is 16.7 wt%.
[0071] The stoichiometric formula of the cathode material is LiNi 0.5 Co 0.01 Mn 0.49 0.01Li 2 MgWO 5 0.005LiPO 2 F 2 .
[0072] The preparation method of the positive electrode material is as follows: lithium nickel cobalt manganese-based oxide is placed in a high-speed mixer, nitrogen protection is turned on (pressure is 0.2MPa), and stirring is continued at a speed of 1200rpm / min; (Li 2 WO 4 ) 0.5 .(Mg(OH) 2 ) 0.5 The aqueous sol is added in the form of a spray and stirred evenly at a low speed; heated to 120°C and dried for 4 hours; stirred at a low speed in an oxygen atmosphere (oxygen concentration is 20%), gradually heated to 450°C, kept warm for 4 hours, and then cooled; when the temperature is cooled to 50°C, stirred at a high speed in a nitrogen atmosphere, lithium difluorophosphate is added, and stirring is continued for 15 minutes to obtain the positive electrode material.
[0073] The present embodiment also provides a soft-pack battery, which uses the positive electrode material provided in the present embodiment as the positive electrode material, PVDF as the binder, activated carbon as the conductive agent, the mass percentage of the three is 96:2:2, N-methylpyrrolidone is used as the solvent, and is stirred into a slurry; the slurry is evenly coated on an aluminum foil by a coating machine, and is made into a positive electrode sheet after drying, the electrolyte is 1.02 mol / L lithium hexafluorophosphate, DMC / EMC, PC solvents and other additives; graphite is used as the negative electrode to make a soft-pack battery.
[0074] Example 3
[0075] This embodiment provides a positive electrode material, and the raw material components for preparing the positive electrode material include 1 kg of lithium nickel cobalt manganese-based oxide, 120 g of (LaOOH) 0.86 ·(TiO(OH) 2 ) 0.14 Aqueous sol and 13.91 g of lithium difluorophosphate.
[0076] The lithium nickel cobalt manganese-based oxide is LiNi 0.35 Co 0.15 Mn 0.50 O 2 , provided by Guangdong Brunp Recycling Technology Co., Ltd.
[0077] (LaOOH) 0.86 ·(TiO(OH) 2 ) 0.14 The solid content in the aqueous sol is 24.5 wt%.
[0078] The stoichiometric formula of the cathode material is LiNi 0.35 Co 0.15 Mn 0.55 O 2 0.03((La 2 O 3 ) 0.86 (TiO2 ) 0.14 )·0.01LiPO 2 F 2 .
[0079] The preparation method of the positive electrode material is as follows: putting lithium nickel cobalt manganese-based oxide into a high-speed mixer, turning on nitrogen protection (pressure is 0.2MPa), and continuously stirring at a speed of 1200rpm / min; (LaOOH) 0.86 ·(TiO(OH) 2 ) 0.14 The aqueous sol is added in the form of a spray and stirred evenly at a low speed; heated to 110°C and dried for 4 hours; stirred at a low speed in an oxygen atmosphere (oxygen concentration is 20%), gradually heated to 250°C, kept warm for 2 hours, and then cooled; when the temperature is cooled to 50°C, stirred at a high speed in a nitrogen atmosphere, lithium difluorophosphate is added, and stirring is continued for 60 minutes to obtain the positive electrode material.
[0080] The present embodiment also provides a soft-pack battery, which uses the positive electrode material provided in the present embodiment as the positive electrode material, PVDF as the binder, activated carbon as the conductive agent, the mass percentage of the three is 96:2:2, N-methylpyrrolidone is used as the solvent, and is stirred into a slurry; the slurry is evenly coated on an aluminum foil by a coating machine, and is made into a positive electrode sheet after drying, the electrolyte is 1.02 mol / L lithium hexafluorophosphate, DMC / EMC, PC solvents and other additives; graphite is used as the negative electrode to make a soft-pack battery.
[0081] Comparative Example 1
[0082] This comparative example provides a soft pack battery, using a positive electrode material of model 712NCM as the positive electrode material (stoichiometric formula is LiNi 0.7 Co 0.1 Mn 0.2 O 2 ), PVDF is a binder, activated carbon is a conductive agent, the mass percentage of the three is 96:2:2, N-methylpyrrolidone is a solvent, and they are stirred into a slurry; the slurry is evenly coated on an aluminum foil using a coating machine, and after drying, a positive electrode sheet is made, the electrolyte is 1.02 mol / L lithium hexafluorophosphate, DMC / EMC, PC solvents and other additives; graphite is used as the negative electrode to make a soft-pack battery.
[0083] Comparative Example 2
[0084] This comparative example provides a soft pack battery, using a positive electrode material of model 523NCM as the positive electrode material (stoichiometric formula is LiNi 0.5 Co 0.2 Mn 0.3 O 2), PVDF is a binder, activated carbon is a conductive agent, the mass percentage of the three is 96:2:2, N-methylpyrrolidone is a solvent, and they are stirred into a slurry; the slurry is evenly coated on an aluminum foil using a coating machine, and after drying, a positive electrode sheet is made, the electrolyte is 1.02 mol / L lithium hexafluorophosphate, DMC / EMC, PC solvents and other additives; graphite is used as the negative electrode to make a soft-pack battery.
[0085] Comparative Example 3
[0086] This comparative example provides a soft pack battery, using a positive electrode material of type 333NCM as the positive electrode material (stoichiometric formula is LiNi 0.33 Co 0.33 Mn 0.33 O 2 ), PVDF is a binder, activated carbon is a conductive agent, the mass percentage of the three is 96:2:2, N-methylpyrrolidone is a solvent, and they are stirred into a slurry; the slurry is evenly coated on an aluminum foil using a coating machine, and after drying, a positive electrode sheet is made, the electrolyte is 1.02 mol / L lithium hexafluorophosphate, DMC / EMC, PC solvents and other additives; graphite is used as the negative electrode to make a soft-pack battery.
[0087] Performance Testing
[0088] 1. The structure of the positive electrode material provided in Example 1 was observed by scanning electron microscopy to obtain Figure 1 Scanning electron micrograph shown.
[0089] in accordance with Figure 1 The positive electrode material includes lithium nickel cobalt manganese-based oxide particles that are approximately spherical, composite oxide particles coated on the surface of the lithium nickel cobalt manganese-based oxide particles, and lithium difluorophosphate particles coated on the composite oxide layer.
[0090] 2. Battery performance test
[0091] Sample: Soft-pack batteries provided in Examples 1-3 and Comparative Examples 1-3
[0092] Test method: After the soft pack battery is formed and aged, the discharge capacity, rate performance, high temperature cycle performance and high temperature storage performance of the battery are tested:
[0093] 1) Test the discharge capacity of soft pack batteries;
[0094] First charge to 4.4V at 0.1C, constant voltage to 0.05C, and discharge to 3.0V at 0.1C rate at room temperature. The initial discharge voltage is 4.4V; record the discharge capacity of the soft-pack battery.
[0095] 2) Test the rate performance of soft pack batteries;
[0096] At room temperature, the battery was charged to 4.4V at a constant current of 0.1C, and then charged to 0.05C at a constant voltage; then discharged to 3.0V at constant currents of 0.1C and 1C, respectively, and the discharge capacity at 0.1C rate and 1C rate were recorded; the ratio of the discharge capacity of the battery at 1C rate to the discharge capacity at 0.1C rate was calculated.
[0097] 3) Testing the high temperature cycle performance of the soft pack batteries provided in Examples 1-3 and Comparative Examples 1-3;
[0098] At a constant temperature of 60°C, in the voltage range of 3.0-4.4V, charge at 1C and discharge at 1C until the capacity retention rate is 80%; the number of continuous cycles at high temperature is recorded.
[0099] 4) Testing the high temperature storage performance of the soft-pack batteries provided in Examples 1-3 and Comparative Examples 1-3;
[0100] The battery cell was fully charged to 4.4V, and then placed in an oven at 80°C for 30 days. The volume of the battery cell before and after baking was recorded, and the volume change rate of the battery after high-temperature baking was calculated using the following formula.
[0101]
[0102] Test results:
[0103] After testing, the discharge capacities of the soft-pack batteries provided in Examples 1-3 and Comparative Examples 1-3 are 205 mAh / g, 180 mAh / g, 165 mAh / g, 196 mAh / g, 178 mAh / g and 160 mAh / g, respectively. This indicates that the discharge capacity of the soft-pack battery provided in Example 1 is equivalent to that of the soft-pack battery provided in Comparative Example 1; the discharge capacity of the soft-pack battery provided in Example 2 is equivalent to that of the soft-pack battery provided in Comparative Example 2; and the discharge capacity of the soft-pack battery provided in Example 3 is equivalent to that of the soft-pack battery provided in Comparative Example 3.
[0104] The ratios of the discharge capacity at 1C rate to the discharge capacity at 0.1C rate of the soft-pack batteries provided in Examples 1-3 and Comparative Examples 1-3 are 93%, 88%, 90%, 85%, 88% and 90%, respectively. This indicates that the rate performance of the soft-pack battery provided in Example 1 is higher than that of the soft-pack battery provided in Comparative Example 1; the rate performance of the soft-pack battery provided in Example 2 is equivalent to that of the soft-pack battery provided in Comparative Example 2; and the discharge capacity of the soft-pack battery provided in Example 3 is equivalent to that of the soft-pack battery provided in Comparative Example 3.
[0105] The number of continuous cycles of the soft-pack batteries provided in Examples 1-3 and Comparative Examples 1-3 at high temperatures are 1600, 2000, 2000, 1000, 1400 and 1600, respectively. It shows that the high-temperature cycle performance of the soft-pack battery provided in Example 1 is better than that of the soft-pack battery provided in Comparative Example 1, which is improved by 60%; the high-temperature cycle performance of the soft-pack battery provided in Example 2 is better than that of the soft-pack battery provided in Comparative Example 2, which is improved by 42.9%; the high-temperature cycle performance of the soft-pack battery provided in Example 3 is better than that of the soft-pack battery provided in Comparative Example 3, which is improved by 25%.
[0106] The volume change rates of the soft-pack batteries provided in Examples 1-3 and Comparative Examples 1-3 after baking at high temperature are 8%, 4%, 3%, 22%, 11% and 8% respectively. It shows that the volume change rate of the soft-pack battery provided in Example 1 after baking at high temperature is much smaller than the volume change rate of the soft-pack battery provided in Comparative Example 1 after baking at high temperature, which is reduced by 63.6%; the volume change rate of the soft-pack battery provided in Example 2 after baking at high temperature is much smaller than the volume change rate of the soft-pack battery provided in Comparative Example 2 after baking at high temperature, which is reduced by 63.6%; the volume change rate of the soft-pack battery provided in Example 3 after baking at high temperature is much smaller than the volume change rate of the soft-pack battery provided in Comparative Example 3 after baking at high temperature, which is reduced by 62.5%. Therefore, the soft-pack battery prepared using the positive electrode material of this embodiment has the advantages of high capacity, high rate, good high-temperature cycle performance and high-temperature stability under 4.4V high voltage, which effectively improves the current situation that the electrochemical performance of general positive electrode materials deteriorates due to structural changes during high voltage cycling and the volume change rate is high due to instability at high temperature.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention and are not limiting. Although the present invention has been described in detail with reference to the above preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A positive electrode material, characterized in that: It includes lithium nickel cobalt manganese-based oxide, composite oxide and lithium difluorophosphate; the composite oxide is coated on the surface of the lithium nickel cobalt manganese-based oxide; the lithium difluorophosphate is coated on the surface of the composite oxide; the composite oxide includes oxygen and at least two metal elements of aluminum, titanium, zirconium, yttrium, tungsten, magnesium, niobium, lanthanum, zinc, tin, calcium or bismuth.
2. The positive electrode material according to claim 1, characterized in that The composite oxide is at least one of Al2O3, TiO2, ZrO2, Y2O3, WO3, LiWO3, SnO, Bi2O3, CaO, La2O3, MgO, LiMgWO5 or MgAl2O4.
3. The positive electrode material according to claim 1, characterized in that The general chemical formula of the lithium nickel cobalt manganese-based oxide is LiNi x Co 1-x-y Mn y O2; x is 0.3-0.8; y is 0.1-0.6; 1-xy is 0.01-0.
4.
4. The positive electrode material according to claim 1, characterized in that The positive electrode material includes lithium nickel cobalt manganese-based oxide, composite oxide and lithium difluorophosphate in a molar ratio of 1:(0.001-0.05):(0.001-0.03).
5. The method for preparing the positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Under an inert atmosphere, a sol of a precursor of at least two elements selected from aluminum, titanium, zirconium, yttrium, tungsten, magnesium, niobium, lanthanum, zinc, tin, calcium or bismuth is added to the lithium nickel cobalt manganese-based oxide in the form of a spray, stirred and mixed at a rate of 600-1500 rpm / min, heated to 80-120° C., and dried for 2-4 hours; In an oxygen atmosphere, stir at a rate of 50-200 rpm / min, heat to 250-450°C, and keep warm for 2-6 hours; Under an inert atmosphere, the temperature is lowered to 30-50° C., lithium difluorophosphate is added, and the mixture is stirred at a rate of 600-1500 rpm / min and mixed for 15-90 minutes to obtain the positive electrode material.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: The precursor includes at least one of metal oxides, hydroxides, composite oxides and / or oxyhydroxides.
7. An electrode slurry, characterized in that: A positive electrode material comprising any one of claims 1 to 4; The positive electrode material is prepared by the preparation method described in claim 5 or 6.
8. An electrode sheet, characterized in that: It includes a current collector and an electrode coating disposed on the current collector; The electrode coating is prepared from the electrode slurry according to claim 7.
9. A method for preparing an electrode sheet, characterized in that: The following steps are involved: The electrode slurry according to claim 7 is coated on the surface of the current collector, dried, and heat-treated to obtain the electrode sheet.
10. Use of the positive electrode material according to any one of claims 1 to 4 in preparing a battery.
Citation Information
Patent Citations
Modified nickel cobalt manganese ternary composite electrode material coated on oxide surface and preparation method thereof
CN107331852A
Nickel cobalt lithium manganate composite positive electrode material and preparation method thereof as well as lithium ion battery
CN108777295A
Dual-oxide compound-coated high-nickel ternary positive electrode material and preparation method thereof
CN108878827A